A two-dimensional fingerprint nanoprobe based on black phosphorus for bio-SERS analysis and chemo-photothermal therapy. Issue 39 (2nd October 2018) - Liu, Zhiming; Chen, Haolin; Jia, Yali; Zhang, Wen; Zhao, Henan; Fan, Wendong; Zhang, Wolun; Zhong, Huiqing; Ni, Yirong; Guo, Zhouyi
Abstract : Flake-shaped nanohybrids based on black phosphorus (BP) have been developed as multifunctional theranostic nanoplatforms for drug delivery, phototherapy and bioimaging. Abstract : Flake-shaped nanohybrids based on black phosphorus (BP) have been developed as multifunctional theranostic nanoplatforms for drug delivery, phototherapy and bioimaging. In this work, we report a facile strategy for fabrication of black phosphorus-Au nanoparticle hybrids (BP-AuNPs), which reveal an extraordinary near-infrared (NIR) photothermal transduction efficiency and drug delivery capacity. The applications of the nanocomposites as therapeutic agents for high-performance chemo-photothermal tumor therapy are accomplished in vitro and in vivo . BP-AuNPs also exhibit wonderful surface-enhanced Raman scattering (SERS) activity under NIR laser excitation with a low Raman background, allowing BP-AuNPs to be used as a promising two-dimensional (2D) fingerprint nanoprobe for bio-SERS analysis. The cellular component identification and label-free live-cell bioimaging based on this type of 2D SERS substrate are generally investigated, which open up promising new perspectives in nanomedicine, including diagnosis, imaging and therapy.